The Reasonable Doubt in Customs and the Limits to its Exercise: How and when to apply it? - Vargas Acuache, Christian (2014)
A Reasonable Doubt is the act by which the Customs communicates the importer that doubts that this has declared the customs value in compliance with the valuation rules properly, requiring information and documentation necessary to verify that they have properly followed the rules valuation. In this article as we explore the conceptual and procedural aspects of management prerogative, we will try to find the limits to their exercise from the time, space and material point of view consistently (in concordance) with the rights and obligations of taxpayers.